Estudio geológico – geotécnico previo a la construcción del relleno sanitario en el sector La Sangui, cantón Celica, provincia de Loja. - Aguilar Velazquez, Evelyn Elizabeth (2023)
The present research project, titled “Estudio geológico – geotécnico previo a la construcción del relleno sanitario en el sector la Sangui, cantón Celica, provincia de Loja” was based on a detailed technical analysis conducted in an area of 3.54 hectares. The study covered various essential aspects to ensure the feasibility and safety of the construction of the civil work, which is of great importance to the canton. A topographic survey of the region was completed as part of the original inquiry, giving a precise depiction of the surface. A slope analysis of the topography was carried out, and the results showed that 48.30% of the ground was steeply inclined. Similar to this, geological characterization was carried out, verifying in the field the existence of basaltic andesites, a characteristic material of the Celica unit, and indicating that the study region is located on this unit. To ascertain the materials' physical-mechanical properties, various in situ tests were performed, including three Standard Penetration Tests (SPT), two lines of seismic refraction, and a test pit for consolidation and direct shear testing. It is worth noting that the execution of these tests was carried out in accordance with applicable regulations to avoid errors in results and obtain greater data precision. With the field-collected information, a desk analysis was conducted, obtaining essential data such as bearing capacity from SPT tests using the Meyerhof and Terzaghi equations, liquidity index, relative consistency, clay behavior based on the liquid limit, plastic limit, plasticity index, and moisture content of the laboratory-analyzed samples from each SPT. Bearing capacity from seismic lines was calculated using the Terzaghi and Tezcan formula, settlement calculations, and shear angle. Therefore, the research project represents a comprehensive study that combines precise geological and geotechnical information to support the proper construction of the sanitary landfill. The results and conclusions obtained through the tests and analyses have a direct impact on the planning and execution of the project, ensuring the sustainability, stability, and long-term functionality of the infrastructure. Keywords: geological, geotechnical, in situ tests, bearing capacity, settlements, shear angle.